(untitled) (Herald of Journalism, 2026)
As artificial intelligence (AI) tools are increasingly integrated into the educational system, debates persist regarding the extent to which these technologies can enhance the learning process and influence students’ cognitive abilities and skills. This article presents an analysis of the evaluative parameters of AI perception among a university audience. The research hypothesis suggests that the rapid proliferation and adoption of AI technologies by students outpace their levels of media literacy and critical thinking. This gap increases the risks of uncritical information consumption, exposure to fake news, and manipulative content. Conversely, educators perceive AI as a risk to student autonomy and academic progress, while acknowledging its valuable instrumental capabilities for specific executive tasks. The purpose of the article is to examine the experiences and forms of AI tool integration in higher education, identify the primary patterns of student attitudes toward AI resources, and describe potential ethical, cognitive, and social risks. The methodological framework of the study comprises a complex of empirical and theoretical methods, including the analysis and systematization of scientific data, sociological surveys, statistical data interpretation, as well as qualitative comparative and summative analyses. The results of the survey research indicate an ambiguous attitude among faculty toward the comprehensive integration of AI into higher education, highlighting significant risks to academic integrity and independent thinking. However, students view AI proficiency as a mandatory component of self-directed learning, an adaptation to new digital media formats, and a vital factor in professional self-development. Given the lack of universally accepted ethical guidelines for the correct use of AI in higher education, this study contributes to the discussion on the most desirable model for AI functioning in education by integrating international standards and recommendations into the Kazakhstani context. The practical significance lies in the substantiation of a promising Augmented Intelligence model, which, in the researchers’ view, is most suitable for educational purposes.